Optimization of patchouli oil extraction by employing design of experiment (DOE) method - Khairul Afif, Bakar @ Ismail (2008)
Patchouli oil is one of the essential oil that has a wide variety of application in cosmetic and aromatherapy industry which used as one important ingredient in perfume and soap. Patchouli also has a potential to be used as an insect repellent and antiseptic product in future. Patchouli oil is obtained using a steam distillation where an aromatic chemical is extracted from patchouli leaves by steam and condensed which provide relatively high yield of product and low cost of running the process. This study is aim to improve a yield of patchouli oil extraction using steam distillation by manipulating the process factor such as extraction time and mass of raw material. The optimization of extraction of patchouli oil is carried out using Response Surface Methodology (RSM) based on Central Composite Design (CCD). Response Surface Methodology is a branch of Design of Experiment (DOE) which a response of interest is influenced by several variables of the process and the main objective of using this method is to find the optimum condition. The optimize condition for steam distillation of patchouli oil was found at 2.38 kg of patchouli leaves and 6.84 hour of extraction time. The yield of 0.6289 percent (weight percent) was achieved using this optimized condition. This gave 67.7 percent increment of yield percentage in comparison to the initial experiment which gives 0.3751 percent of yield.